The relationship of high school graduation exams to graduation rates and SAT scores. - Marchant, Gregory J.; Paulson, Sharon E. (Education Policy Analysis Archives, 2005)
The current study examined the effect of high school graduation exams on states' graduation rates, states' aggregated SAT scores, and individual students' SAT scores. Three data sources were used: One source identified states requiring a standardized test for graduation; the NCES provided state aggregated data on graduation rates for the class of 2002; and the College Board provided its 2001 SAT database for all test-takers. After controlling for students' demographic characteristics (e.g., race, family education and income, GPA and class rank), regression analyses revealed that states requiring graduation exams had lower graduation rates and lower SAT scores. Individually, students from states requiring a graduation exam performed more poorly on the SAT than did students from states not requiring an exam. The impact of high stakes tests' on students' motivation to stay in school and on the teaching of critical thinking skills (tested by the SAT) are discussed.